Analisis Eufemisme dan Disfemisme dalam Berita Kriminal di Media Tempo.Co dan Merdeka.Com Pembelajaran Teks Berita: Euphemisms and Dysphemisms in Criminal News Reporting: A Comparative Linguistic Analysis of Tempo.Co and Merdeka.Com - Sa’adah, Laelatus; Herlina, Dewi; Rosalina, Sinta (Universitas Tidar, 2025)
This study examines the use of euphemisms and dysphethes in crime news in Tempo.co and Merdeka.com online media, focusing on their impact on readers' perceptions. The question asked is how these two linguistic strategies affect the delivery of information and audience reactions. The purpose of this study is to identify the forms of euphemism and dysphemism used and evaluate their relevance in learning news texts. The research method used is qualitative descriptive, with data collection through news documentation from both media. The sample consisted of crime news containing euphemisms and dysphemisms, and data analysis was carried out using the content analysis method. The results showed that Tempo.co used euphemisms more to maintain neutrality and professionalism, while Merdeka.com tended to use dysphemism to create dramatic and attention-grabbing effects. These findings indicate that the choice of language style not only creates the atmosphere of the news, but also shapes the emotional response of readers. This research is expected to provide new insights in understanding the dynamics of language use in mass media and enrich teaching materials in Indonesian language learning. The results of the research can be generalized in linguistic studies and make a significant contribution to ethical journalistic practice.